2014
DOI: 10.1155/2014/424923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recycling Protocol on Mechanical Strength of Used Mini-Implants

Abstract: Purpose. This study evaluated the influence of recycling process on the torsional strength of mini-implants. Materials and Methods. Two hundred mini-implants were divided into 4 groups with 50 screws equally distributed in five diameters (1.3 to 1.7 mm): control group (CG): unused mini-implants, G1: mini-implants inserted in pig iliac bone and removed, G2: same protocol of group 1 followed by sonication for cleaning and autoclave sterilization, and G3: same insertion protocol of group 1 followed by sonication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It was also suggested that, by mechanical stripping, the surface of a used implant is better cleaned. Regarding its effect on the mechanical properties, it has been suggested [3,23] that the removal torque was increased while, the fracture torque was not modified [6]. We found statistically significant greater insertion torque for the sandblasted Link mini-implants (26.94 Ncm) and lower insertion torque for Yesanchor (36.46 Ncm) implants.…”
Section: Resultsmentioning
confidence: 46%
See 4 more Smart Citations
“…It was also suggested that, by mechanical stripping, the surface of a used implant is better cleaned. Regarding its effect on the mechanical properties, it has been suggested [3,23] that the removal torque was increased while, the fracture torque was not modified [6]. We found statistically significant greater insertion torque for the sandblasted Link mini-implants (26.94 Ncm) and lower insertion torque for Yesanchor (36.46 Ncm) implants.…”
Section: Resultsmentioning
confidence: 46%
“…Analyzing the effect of the sonification to the mechanical properties of a mini-implant, it can be concluded that, in both types (Link and Yesanchor), the maximum insertion torque slightly but not significantly decreased. Estelita et al [6] compared the fracture torque of the new and ultrasonically cleaned miniimplants fracture torque and revealed no significant differnces. Group G2 underwent chemical cleaning with phosphoric acid.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations